Assessment of Silicone Oil Emulsification: A Comparison of Currently Applied Methods - Hongmei Zhao; Qian Chen; Jian Yu; Kaicheng Wu; Yuan Zong; Chunhui Jiang; Haohao Zhu; Gezhi Xu (Journal of Ophthalmology)
Purpose. To compare ultrasound biomicroscopy (UBM), Coulter counter, and B-scan ultrasonography in the evaluation of silicone oil (SO) emulsification. Methods. Patients who underwent primary pars plana vitrectomy with SO tamponade for rhegmatogenous retinal detachment and SO removal were included. UBM images were acquired before the SO removal, and B-scan images were taken after removal. The number of droplets in the first and last 2 mL of washout fluid was analyzed using a Coulter counter. The correlations between these measurements were analyzed. Results. Thirty-four eyes received both UBM and Coulter counter analysis for the first 2 mL of washout fluid, and 34 underwent B-scan and Coulter counter analysis of the last 2 mL washout fluid. The mean UBM grading was 26.41 ± 9.71 (range: 1–36); the mean SO index obtained with B-scan was 5.25 ± 5.00% (range: 0.10–16.49%), and the mean number of SO droplets was 1.26 ± 2.45 × 107/mL and 3.34 ± 4.22 × 106/mL in the first and last 2 mL of washout fluid, respectively. There were significant correlations between UBM grading and SO droplets in the first 2 mL and between B-scan grading and SO droplets in the last 2 mL (all P<0.05). Conclusions. UBM, Coulter counter, and B-scan ultrasonography could all be used in the evaluation of SO emulsification, and their findings were comparable.